Methamphetamine-sensitized rats show augmented dopamine release to methylphenidate stimulation: A positron emission tomography using [18F]fallypride. Issue 1 (30th April 2015) - Ota, Miho; Ogawa, Shintaro; Kato, Koichi; Wakabayashi, Chisato; Kunugi, Hiroshi
Abstract: Previous studies demonstrated that patients with schizophrenia show greater sensitivity to psychostimulants than healthy subjects. Sensitization to psychostimulants and resultant alteration of dopaminergic neurotransmission in rodents have been suggested as a useful model of schizophrenia. This study was aimed to examine the use of methylphenidate as a psychostimulant to induce dopamine release and that of [ 18 F]fallypride as a radioligand to estimate the release in a rat model of schizophrenia. Six rats were scanned by positron emission tomography (PET) twice before and after methylphenidate challenge to evaluate dopamine release. After the scans, these rats were sensitized by using repeated methamphetamine (MAP) administration. Then, they were re-scanned twice again before and after methylphenidate challenge to evaluate whether MAP-sensitized rats show greater sensitivity to methylphenidate. We revealed a main effect of MAP-pretreatment and that of metylphenidate challenge. We found that % change of distribution volume ratio after repeated administration of MAP was greater than that before sensitization. These results suggest that methylphenidate-induced striatal dopamine release increased after sensitization to MAP. PET scan using [ 18 F]fallypride at methylphenidate-challenge may provide a biological marker for schizophrenia and be useful to diagnose schizophrenia. Highlights: We estimated the dopamine release in a rat model of schizophrenia using with PET. To evaluate dopamine release, we scanned pre- and post-methylphenidate challenge. These rats were sensitized by methamphetamine and were used as schizophrenia model. They were re-scanned to evaluate the increase of sensitivity to methylphenidate. We showed that the methylphenidate sensitivity was increased after sensitization.